The convection of unsteady casson fluid over an infinite inclined isothermal plate - Husna Izzati, Osman; Nur Fatihah, Mod Omar; D., Vieru; Zulkhibri, Ismail (2022)
An analytical solution of chemical reaction on unsteady Casson fluid over an infinite inclined isothermal plate has been presented in this article. Laplace transform technique has been used in this study to obtain the results of velocity, temperature and concentration. The analytical solution for governing equations are solved by using this method. The effects of various embedded solution on velocity, temperature and concentration such as chemical reaction, magnetic parameter and radiation has been discussed graphically with numerical results.